Epidemiology and Performances of Typhidot Immunoassay and Widal Slide Agglutination in the Diagnosis of Typhoid Fever in Febrile Patients in Bafoussam City, Cameroon: A Cross-Sectional Comparative Study - Aurelie Dahlia Yemeli Piankeu; Siméon Pierre Chegaing Fodouop; Michel Noubom; Emmanuel Boris Gomseu Djoumsie; Georges Ful Kuh; Donatien Gatsing (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. Enteric fever is a great public health problem associated with significant illness and death in many endemic countries, and its clinical diagnosis is still daunting. The aim of this study was to determine the prevalence and risk factors of S. Typhi among febrile patients in Bafoussam and to evaluate the diagnostic performances of Widal and Typhidot tests. Methods. This was a cross-sectional study among 336 participants visiting three hospitals in Bafoussam from August 1, 2021, to November 31, 2021. Widal test, Typhidot assay, and stool culture were used to screen for salmonellosis with the help of a structured questionnaire. Results. The prevalence of S. Typhi and S. Paratyphi was found to be 62.85% and 37.14%, respectively. The overall prevalence of typhoid fever using stool culture was 20.86%. The significant risk factors associated with enteric fever were lack or insufficient knowledge of typhoid fever, poor hand hygiene, and anorexia. Typhidot immunoassay was more sensitive (100%) and specific (82.3%) than the Widal test. Both were analytically inferior to stool culture. Conclusions. High prevalence of typhoid fever (20.86%) was observed which was largely associated with lack or insufficient knowledge of typhoid fever, poor hygiene measure, and anorexia as risk factors. The performances of the Widal and Typhidot test against a stool culture were inferior but with Typhidot better than the Widal slide agglutination.